IMPLEMENTASI KEBIJAKAN ALOKASI DANA GAMPONG (ADG) DALAM MENINGKATKAN PEMBANGUNAN DI KAB. ACEH BARAT - ADUWINA PAKEH (Jurnal Public Policy, 2016)
Law No. 06 of 2014 on the village said that the source of income of the village consists of a). Revenue native village consisting of; results of operations of the village, the wealth of the village, the result of self-help and participation, the results of gotong royong, and other legitimate revenue villages; b). Tax-sharing districts / cities of at least 10% of the levy for the village and district / city mostly reserved for the village; c). Part of the financial balance of central and local received by the district / city to the village at least 10% which distribution proportionally to each village which is the Village Fund Allocation; d). Financial assistance from the government, provincial government, regency / municipal government in the implementation of government affairs; e). grants and donations from third parties that are not binding. The purpose of this study is to describe and analyze the implementation of Government policy on the Village Fund Budget (ADD) –The Village Fund Allocation (ADG - Government of Aceh) in the Village Pante Ceureumen West Aceh District. Based on the results, it can be concluded that development plan is not yet fully meet aspirations of society with mutual trust and open.The activities conducted in the public aspirations village level so that only representatives of the community is able to convey the problems and needs facing. Only a small portion is in the village of Pante Ceureumen who have to meet the aspirations of the mutual trust and open.  Keywords: Implementation, Policy, The Village Fund Allocation (ADG), the Village, Pante Ceureumen